A conventional & deep learning strategy for analyzing & detecting Bengali fake news in online medium - Ahmed, Istiak; Prima, Shanzida Binta Akram; Baptee, Tahsin Anzum; Afroz, Mehrin; Shanto, Ariful Islam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.